Pengaruh Personal Selling, Respon Nasabah dan Minat Nasabah Terhadap Keputusan Nasabah dalam Mengaktifkan Aplikasi BRImo Mobile Banking - Saryadi Saryadi; Indra Hastuti; Liss Dyah Dewi Arini (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to determine the influence of personal selling, customer response, and customer interest on customer decisions in activating the BRImo application. Research is a type of quantitative research. A sample of 100 respondents using GForm from a total population of 3100. by accidental random sampling. The method uses multiple linear regression with statistical tests and classical assumptions. Classic assumptions are not a problem. The results showed that customer responses and customer interest were significantly positive in influencing customer decisions in activating the BRImo application, while personal selling had a positive effect was not significant. The F test shows that the simultaneous influence of personal selling, customer response and customer interest in customer decisions is significant, which is 70.298 with a significant value of 0.00< 0.05. The coefficient of determination is 0.687. This shows that the customer's decision can be explained by 68.7% by personal selling, customer response, and customer interest. The remaining 0.313 or 3.13% is explained by other variables outside the model, such as customer knowledge and education. The most dominant variable in influencing customer decisions is the customer response, which is shown to be a regression coefficient of 0.354 with a t-count of 4.153.